STRATEGI GURU PAI DALAM MENGATASI KESULITAN MEMBACA AL-QUR’AN PADA PESERTA DIDIK DI MTS ARIFAH GOWA - Saputra Syachrul, Muh Ilham; Fattah, Abdul; Rusyd, Rajiah (LPPM Universitas Islam 45, 2024)
The purpose of this study was to determine the learning of the Qur'an in students, the factors of students' difficulties in reading the Qur'an and the PAI teacher's strategy in overcoming difficulties in reading the Qur'an at MTs Arifah Gowa. This research method uses field research with a qualitative approach. The data needed in this study used the main instrument in the form of interviews, while observation and documentation were used to complement the data needed. All data collected were analysed in the form of data reduction, data presentation, and verification or conclusion drawing in a qualitative descriptive manner. The results showed that PAI teachers at MTs Arifah Gowa used the lecture method, assignment method, iqro method, practice method of reading al-qur'an habituation. The method of learning Islamic religious education, especially in the subject of al-qur'an which is often used by teachers is the method of demonstration and lecture. The factors that influence the difficulty of reading the Qur'an are students' self-awareness and motivation, lack of attention and education from parents, the negative influence of high technology so that students are carried away with things that are not useful compared to learning to read the Qur'an. Students' difficulties in reading the Qur'an are not recognising the hijaiyah letters, it is difficult to distinguish the short length of the Qur'anic recitation. The strategy is carried out to foster students, namely at the beginning of each lesson the teacher does tahsin qiraah or corrects the reading of the Qur'an.